-(6m-2)+2(8-4m)=-3m-5m

Simple and best practice solution for -(6m-2)+2(8-4m)=-3m-5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6m-2)+2(8-4m)=-3m-5m equation:



-(6m-2)+2(8-4m)=-3m-5m
We move all terms to the left:
-(6m-2)+2(8-4m)-(-3m-5m)=0
We add all the numbers together, and all the variables
-(6m-2)+2(-4m+8)-(-8m)=0
We multiply parentheses
-(6m-2)-8m-(-8m)+16=0
We get rid of parentheses
-6m-8m+8m+2+16=0
We add all the numbers together, and all the variables
-6m+18=0
We move all terms containing m to the left, all other terms to the right
-6m=-18
m=-18/-6
m=+3

See similar equations:

| (6x-11)=(2x-9) | | C(x)=62500+500x+x^2 | | -3f=-2f−4 | | C(x)=62500+500x+x2 | | 6x+46=4x+54 | | -4x-4(x-2)=6(x-8) | | x+3=4x-28 | | -3v-7(-5v-8)=-3v-3(-v-8) | | 16x=(9x+5) | | -3m=10−4m | | -20+23=m-8 | | -6j=-10j+8 | | x/2+x/3=7. | | 6. x/2+x/3=7. | | a-7=32 | | 5x+8+6x−6=90 | | 1/4(5b+11)=11 | | 15y+7=15y+7 | | 2/5x-1/2x+4=3/10x-2 | | 2x-6-17=10x-20 | | 2x-6-17=10x-2@ | | -13+23=m-8 | | 8^x=9^x-2 | | 5.6x+10-7.6x=2 | | 5k=6+2k | | 90+x34+x+64=180 | | 20x-2x=10-3x | | 8-0.8x=8 | | 2/x+3-5x+6/x-1=9x-5/x2+2x-3 | | 2x-1/3=3x+2/3 | | -5+-15y=1 | | (x-3)^2(x+1)^4(2x+1)^4(3x+2)=0 |

Equations solver categories